2020
DOI: 10.21608/ejhc.2020.106973
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health Promoting Behaviors among Faculty of Nursing Students

Abstract: Background: Nursing students are considered as health care providers and role models in society and their behavior influence the quality of care that is provided by them. In addition, Health promoting behaviors among the nursing students may affect the quality of patient education. Aim of the study was to assess the health promoting behaviors among faculty of nursing students. Research design: A descriptive research design was utilized. Setting: The study was carried out at Faculty of Nursing affiliated to Ain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 2 publications
2
4
1
Order By: Relevance
“…The majority of them were worked. This finding was in disagreement with Abozeid, et al, (2020) who studied assessment of health promoting life styles practices among faculty of nursing in Egypt that reported that (48.6%) of the mean age of students was 20.8±2.3 years, (95.4%) were single. Moreover, related to academic year (33%) of students were at second year.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…The majority of them were worked. This finding was in disagreement with Abozeid, et al, (2020) who studied assessment of health promoting life styles practices among faculty of nursing in Egypt that reported that (48.6%) of the mean age of students was 20.8±2.3 years, (95.4%) were single. Moreover, related to academic year (33%) of students were at second year.…”
Section: Discussioncontrasting
confidence: 68%
“…Also, there was a significant correlation between sex, academic year, type of family and father occupation of studied students and their health promoting lifestyles score after program intervention as (P value≤ 0.05).This finding was in the same line with Abozaid et al, (2020) who showed that, a highly significant difference between the total health promoting behaviors of the studied students and their age, academic year, accommodation type and residence (P≤0.01) were observed. While, there was statistically significant relation with their sex and marital status at p < 0.05(Abozeid et al, 2020) ConclusionAccording to the findings of the present study, the educational program was effective and improved the adherence level to healthy lifestyle practices among studied students through the study stages. Furthermore, the current study revealed that there was a highly statistical difference with significantly among the studied students in all Pender's determinants score of healthy behaviors before and after three months postprogram intervention.Recommendations:Lectures, workshops, and campaigns with periodic refreshment in service training should be regularly organized to empowering undergraduate students in different faculties in order to equip them with adequate knowledge on health promotion lifestyles behaviors.…”
supporting
confidence: 77%
See 3 more Smart Citations